2017
DOI: 10.1007/s12350-016-0761-3
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive PET quantitative myocardial blood flow with regadenoson for assessing cardiac allograft vasculopathy in orthotopic heart transplantation patients

Abstract: Background Risk stratification and early detection of cardiac allograft vasculopathy (CAV) is essential in orthotopic heart transplantation (OHT) patients. This study assesses the changes in myocardial blood flow (MBF) noninvasively in OHT patients using quantitative cardiac PET with regadenoson. Methods Twelve patients (Group 1) (8 males, 4 females, mean age 55 ± 7 y) with no history of post OHT myocardial ischemia were enrolled after 5.4± 2.0 y after OHT. Fifteen patients (Group 2) (9 males, 6 females, mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…5 ). In a comparison study among PET, IVUS and ICA, 82 Rb-dipiridamole PET test demonstrated that the reduction in MBF and the concurrent increase in coronary resistance were highly suggestive of CAV, with > 96% specificity [ 77 ]. Moreover, myocardial flow reserve quantification using 13 NH 3 was inversely related to the volume of coronary plaques as estimated by IVUS, also when ICA was negative [ 78 ].…”
Section: Nuclear Imagingmentioning
confidence: 99%
“…5 ). In a comparison study among PET, IVUS and ICA, 82 Rb-dipiridamole PET test demonstrated that the reduction in MBF and the concurrent increase in coronary resistance were highly suggestive of CAV, with > 96% specificity [ 77 ]. Moreover, myocardial flow reserve quantification using 13 NH 3 was inversely related to the volume of coronary plaques as estimated by IVUS, also when ICA was negative [ 78 ].…”
Section: Nuclear Imagingmentioning
confidence: 99%
“…13 NH 3 is another excellent PET perfusion tracer with high extraction. Although there are a few cardiac PET studies in which regadenoson has been used together with 15 O-water 27 or 13 NH 3 PET, [28][29][30] there are no previous comparisons of the hyperemic effect of regadenoson versus adenosine or dipyridamole using an ideal PET perfusion tracer.…”
Section: Discussionmentioning
confidence: 99%
“…Stress MBF alone showed its role in detecting CAD 82,84 and was a potent outcome predictor of hypertrophic cardiomyopathy 85 . Elevated rest MBF was observed in patients with orthotopic heart transplantation, 86 and abnormal rest MBF was associated with major adverse cardiovascular outcomes such as unstable angina, non-ST and ST-elevation myocardial infarction, and stroke 87 …”
Section: Quantification Parameters—mbf Cfr and Their Utilitiesmentioning
confidence: 99%
“…Stress MBF alone showed its role in detecting CAD 82,84 and was a potent outcome predictor of hypertrophic cardiomyopathy. 85 Elevated rest MBF was observed in patients with orthotopic heart transplantation, 86 and abnormal rest MBF was associated with major adverse cardiovascular outcomes such as unstable angina, non-ST and ST-elevation myocardial infarction, and stroke. 87 Also, because of the nature of tissue compartment models, absolute quantification like MBF in a physical unit of flow (/min) does not depend on accurate measurement of administrated activity because activity values are all cancelled out during kinetic modeling computation.…”
Section: Quantification Parameters-mbf Cfr and Their Utilitiesmentioning
confidence: 99%